2021
DOI: 10.1038/s41379-020-0644-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three PD-L1 immunohistochemical assays in head and neck squamous cell carcinoma (HNSCC)

Abstract: Expression of programmed cell death-ligand 1 (PD-L1) is being used as predictive biomarker for immunotherapy in head and neck squamous cell carcinoma (HNSCC). Several antibodies are available for PD-L1 testing and multiple staining and scoring methods are used. This study aimed to compare the performance of two PD-L1 standardized assays (SP263 and 22C3 pharmDx) and one laboratory-developed test (LDT) (22C3) in HNSCC using the tumor proportion score (TPS) and the combined positive score (CPS). Pretreatment biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 19 publications
7
85
1
2
Order By: Relevance
“…A third study reported values between 73% and 98% from applying different positivity scores and cut-offs for each antibody clone used [ 9 ]. Recently, a large study demonstrated that the SP263 clone stained a higher percentage of cells, especially when the CPS was employed [ 17 ]. Moderate concordance was shown between three different PD-L1 assays, and considerable differences in PD-L1 positivity were observed when using clinically relevant cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…A third study reported values between 73% and 98% from applying different positivity scores and cut-offs for each antibody clone used [ 9 ]. Recently, a large study demonstrated that the SP263 clone stained a higher percentage of cells, especially when the CPS was employed [ 17 ]. Moderate concordance was shown between three different PD-L1 assays, and considerable differences in PD-L1 positivity were observed when using clinically relevant cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to lung cancer, evidence for direct comparison among assays in HNSCC is scarce. De Ruiter at al 20 . compared the reference 22C3 assay with a 22C3 laboratory developed test (LDT) and the SP263 assay in 143 cases.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in NSCLC, PD-L1 expression has been recently associated with the anatomical site of the biopsy, and its predictive value is also different for each site [ 120 ]. On the other hand, a recent comparative study among three different PD-L1 IHC assays showed moderate concordance among the assays and considerable differences in PD-L1 positivity [ 121 ]. The recent findings suggest that TEXs carrying functional PD-L1 can induce immunosuppression inhibiting Teff cells [ 122 ].…”
Section: Biomarkers Of Response To Immunotherapy In Hnsccmentioning
confidence: 99%